EVALUASI KURIKULUM PJOK BERBASIS MODEL CONTEXS, INPUT, PROSESS, PRODUCT DI SMA NEGERI 22 GARUT DAN SMA SWASTA AL - MUSADDADIYAH GARUT - Fazar Rijal Firdaus, - (2022)
This research includes evaluative research, the purpose of this study is to evaluate the PJOK curriculum at the education unit level. The design of this research is an evaluative research using the CIPP model (context, input, process, product). The method used in this research is descriptive quantitative. The population in this study was the Principal, PJOK Subject Teachers, Students and Parents of Students at SMA Negeri Garut and SMA Swasta Al -Musaddadiyah Garut, the samples in this study were Principals, Subject Teachers PJOK, 30 students and 30 parents of students. in SMA Negeri Garut and SMA Al-Musaddadiyah Garut, the sampling technique used was random sampling. The research instrument used a questionnaire and interviews were given to the principals, PJOK teachers, students and parents of students. Data analysis was carried out quantitatively, using T-scores, then compared to the Glickman quadrant. The results of the data analysis of the evaluation of the PJOK curriculum at SMA Negeri 22 Garut showed it was quite effective with the results being in quadrant II (+ - + + ), and at SMA Sawasta Al - Musaddadiyah Garut showed it was effective with results in quadrant I (+ + + +)